2015
DOI: 10.1007/s10522-015-9570-3
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of reactive oxygen species accumulation by depletion of superoxide dismutases with age-dependent impairment in the nervous system and muscles of Drosophila adults

Abstract: The theory that accumulation of reactive oxygen species (ROS) in internal organs is a major promoter of aging has been considered negatively. However, it is still controversial whether overexpression of superoxide dismutases (SODs), which remove ROS, extends the lifespan in Drosophila adults. We examined whether ROS accumulation by depletion of Cu/Zn-SOD (SOD1) or Mn-SOD (SOD2) influenced age-related impairment of the nervous system and muscles in Drosophila. We confirmed the efficient depletion of Sod1 and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 49 publications
1
53
0
1
Order By: Relevance
“…SOD1 localizes to the cytoplasm, SOD2 to the in the mitochondrial matrix, and SOD3 to the extracellular space. Loss of either SOD1 or SOD2 causes early lethality in flies and mice [30, 31], whereas ubiquitous overexpression of either SOD1 or SOD2 extends lifespan [32–36]. This is in line with our findings that boss mutant flies have increased oxidative stress levels and increased sensitivity to oxidative stress.…”
Section: Resultssupporting
confidence: 87%
“…SOD1 localizes to the cytoplasm, SOD2 to the in the mitochondrial matrix, and SOD3 to the extracellular space. Loss of either SOD1 or SOD2 causes early lethality in flies and mice [30, 31], whereas ubiquitous overexpression of either SOD1 or SOD2 extends lifespan [32–36]. This is in line with our findings that boss mutant flies have increased oxidative stress levels and increased sensitivity to oxidative stress.…”
Section: Resultssupporting
confidence: 87%
“…Seminal experiments showed that genetic manipulation of catalase and superoxide dismutase protein SOD could alter lifespan in the fly [32, 35]. The systemic and cell specific effects of catalase and SOD in the fly are not yet fully clear and adult muscle specific expression of these proteins has not been assayed in homogenized genetic background conditions.…”
Section: Mitochondrial Dysfunction and Oxidative Stress In Aged Mumentioning
confidence: 99%
“…However, other studies support the deleterious role of ROS on aging. Very recent studies performed in Drosophila showed that depletion of SOD1 and SOD2 in muscle and nervous system produced ROS accumulation, impairment of locomotive activity and shortened lifespan (Oka et al 2015). Then, the role of ROS in longevity in Drosophila is also not clear and different studies show controverted results.…”
Section: Ageing In Drosophila Melanogastermentioning
confidence: 99%